(untitled) (Journal of Medical Sciences, 2022)
The Antibiotics are not used to treat infectious disease caused by viruses, but it can also be prescribed for treating the infections caused by bacteria. The patient on ventilation is at risk for nosocomial pathogen and they need an urgent antibiotic intervention. In this study we aimed to find out the etiologies of secondary bacterial infection and the clinical outcome of COVID-19 patients admitted to isolation department, Sebha Medical Center (SMC). Eight patients (8/50) showed increased the inflammatory markers after 48hrs of admission. The antibiotic culture sensitivity profile showed that the gram-negative bacteria (Pseudomonas spp., Acinetobacter bumannii, Stenotrophomonas maltophil) were the predominant. 2/8 of the critically ill patient were improved and home discharged. The remaining (6/8) was deteriorated due to multidrug resistant bacteria infection and they did not receive the appropriate antibiotics.